X-RAY PHASE ANALYSIS OF PHOSPHORITES TREATED WITH UREA NITRATE SALT AND NITRIC ACID (Scientific journal of the Fergana State University, 2023)
This article presents analysis of the effect of urea nitrate salt and nitric acid solutions on low-grade phosphorites of Central Kyzylkum and the results of X-ray phase analysis of their products. Changes in the composition of the samples were studied by X-ray phase analysis, the degrees of their crystallinity and amorphousness, relative changes, and particle sizes were calculated. According to the results, data, their analyses and conclusions are presented on a decrease in the content of the crystalline phase in the solid states of low-quality samples of phosphorites subjected to soaking with urea nitrate and nitric acid, and an increase in the content of the amorphous phase by 5-10%, which increases the digestibility of the main nutrient element in phosphorites P2O5 and CaO, MgO.